Smartcard as a payment Alternative: A Diffusion of Innovation Perspective - Yusman, Tina (2002)
The main principal of the study is to determine the perception of innovation characteristics and see whether they differ between adopters and non-adopters of SmartCard. Smar Card was chosen in this study mainly because of its newness and the importance of such innovation be studied. Due to this, innovativeness was also chosen to be a part of this study. Innovativeness was measured using the Domain Specific Innovativeness Scale by Goldsmith and Hofacker (1991) for its sound psychometric values. Innovation characteristics on the other hand were measured using II-item measurement proposed by Rogers (1983). Cronbach's alpha showed a value of 0.7337 with Kaiser-Meyer-Olkin Measure of Sample adequacy revealed a value of 0.725. The result of the study revealed that, using ANOVA. demographic variables such as race and age have an impact on innovativeness which give rise to the fact that culture, nationalism and emotions does affect innovativeness than the more tangible values. Difference in innovativeness was also detected between the adopters and non-adopters with the adopter of SmartCard being more innovative. Wilk's Lambda showed a value of 0.861. Innovativeness was also found to be correlated with innovation characteristics, which means that how a person perceives an innovation depends on how innovative a person is. Lastly using Discriminant analysis, it was discovered that there are significant differences in the perception between both adopters and non-adopters with Wilk's Lambda value of 0.773. Perception was found to be the key in determining whether an innovation will be successfully diffused or the opposite. The authorities may view SmartCard as beneficial but the consumers may not The result of this study showed that both adopters and non-adopter held different views with regard to SmartCard thus; appropriate promotion strategy is deemed desirable. It is also hoped that the findings in this study will bridge the gap between theoretical perspective and managerial perspective ending speculation that any university research offers little practical values.